Coda: The “Queen Under the Hill,” or, Robert Duncan’s Lesson in Essential Autobiography - Rob Halpern (Sillages Critiques)
This is a hybrid work of creative scholarship: a lyrical essay that blends personal history with literary criticism. In it, I question my apprenticeship with Duncan when I was a young twenty-something, as I was struggling to understand what it might mean to be a “good gay poet.” In 1987, I traveled with a copy of Duncan’s The Opening of the Field, and while I could not fully comprehend the poems, the book nevertheless offered me a model – for better and for worse – for sublimating my sexuality during the worst years of the AIDS crisis. Now, thirty-two years later, I return to Duncan’s first “mature” work in an effort to better understand both the book and myself.